2014
DOI: 10.4103/0300-1652.137228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison effect of intravenous tranexamic acid and misoprostol for postpartum haemorrhage

Abstract: Background:Postpartum haemorrhage (PPH) is the third-most common cause of maternal death in the United States and it is still the first prevalent cause of maternal death in developing countries. Active prevention of haemorrhage with an uterotonic or other new drugs leads to a decrease in postpartum vaginal haemorrhage. The aim of this study was to compare anti-haemorrhagic effect of Tranexamic acid (TXA) and Misoprostol for PPH.Patients and Methods:In a double-blinded randomised control clinical trial, 200 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
(25 reference statements)
3
7
2
Order By: Relevance
“…Sahhaf et al [21] findings contradicting the present study and found that haemoglobin levels and bleeding volume were similar in both misoprostol after 6-12 hours and intravenous TA. The disparity could be attributed to alterations in the sort and dosage of misoprostol managed.…”
Section: Discussioncontrasting
confidence: 99%
“…Sahhaf et al [21] findings contradicting the present study and found that haemoglobin levels and bleeding volume were similar in both misoprostol after 6-12 hours and intravenous TA. The disparity could be attributed to alterations in the sort and dosage of misoprostol managed.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are supported by another study that revealed that TXA reduced the requirement for additional uterotonic agents compared to the control group, with a rate of (4.2% vs. 7.3%) 30 . In contrast, Misoprostol does not demonstrate any specific preference for TXA 20 .…”
Section: Discussionmentioning
confidence: 63%
“…Sahhaf et al found no significant differences between misoprostol and tranexamic acid group in haemorrhage during labour, postpartum haemoglobin level, and discharge haemoglobin level, and stated that Misoprostol has no specific preferences to TXA. 9 The differences in results may be due to the type and dosage of administered drugs. Bose et al found statistically insignificant reduction in blood loss in the TXA group compared with the misoprostol group, irrespective of the presence or absence of high-risk factors (470.30 vs 491.74 mL, p=0.487).…”
Section: Discussionmentioning
confidence: 99%
“…Sahhaf et al found no significant differences between misoprostol to TXA and suggested more studies with a greater population. 9 Therefore, this study was designed to evaluate and compare the efficacy of these two therapeutic options in controlling blood loss following CS.…”
Section: Introductionmentioning
confidence: 99%